New species and new report of Hyalella S. I. Smith, 1874 (Crustacea: Amphipoda: Dogielinotidae) from Minas Gerais state, Southeastern Brazil - Bastos-Pereira, Rafaela; de Pádua Bueno, Alessandra Angélica (Zootaxa, 2012)
At present, 13 species of Hyalella are recorded from Brazilian hydrographic basins. A new species of the genus was foundin the municipality of Arcos, Minas Gerais state and it is described here. Curved seta on inner ramus of male uropod 1,posterior margin of gnathopod 2 propodus shorter than palm, telson longer than wide are some of the diagnostic charatctersof this new species. The articles of maxillipod palp and propodus of gnathopod 2 are elongated as observed in H.longistila,but the new species differs from it because of the curved seta on uropod 1. Despite being large and diverse group, Hyalellais represented only by two species in the state of Minas Gerais (Southeastern Brazil), H. warminig and H. gracilicornis.The distribution of H. longistila, previously recorded in Rio de Janeiro state, was extended to Minas Gerais state. Thiswork, therefore, contributes for the knowledge of Amphipoda fauna from Brazil, describing a new species and providing a key to the species identification. From this work, the number of Hyalella species found in Brazil to 14.